2013
DOI: 10.4322/nutrire.2013.015
|View full text |Cite
|
Sign up to set email alerts
|

Letramento nutricional: desempenho de dois grupos populacionais brasileiros

Abstract: In this study, we aimed to compare the level of nutritional literacy of two different population groups. It is a cross-sectional quantitative study with secondary data analysis. We investigated 140 individuals, both male and female, divided in two groups: 70 were customers of a mall (Group 1) and 70 were patients of the National Health System-NHS (Group 2) in Fortaleza, Ceará state, Brazil. The level of nutritional literacy was determined by the Nutritional Literacy Scale (NLS) questionnaire, which was transla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
(24 reference statements)
0
4
0
3
Order By: Relevance
“…As mulheres apresentaram, em sua maioria (83,3%), LA adequado, independente de sua raça/cor. A prevalência de 16,7% de LA marginal e nenhuma participante com LAinadequado é um pouco maior do que a encontrada por Sampaio et al (2013), primeiro estudo nacional a verificar o nível de LA. No estudo destes autores a prevalência de LA marginal foi de 4,3% entre frequentadores de um shopping center localizado em bairro que aglomera pessoas de alto poder aquisitivo na cidade de Fortaleza, Ceará, e de 10,0% entre usuários do Sistema Único de Saúde (SUS).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…As mulheres apresentaram, em sua maioria (83,3%), LA adequado, independente de sua raça/cor. A prevalência de 16,7% de LA marginal e nenhuma participante com LAinadequado é um pouco maior do que a encontrada por Sampaio et al (2013), primeiro estudo nacional a verificar o nível de LA. No estudo destes autores a prevalência de LA marginal foi de 4,3% entre frequentadores de um shopping center localizado em bairro que aglomera pessoas de alto poder aquisitivo na cidade de Fortaleza, Ceará, e de 10,0% entre usuários do Sistema Único de Saúde (SUS).…”
Section: Discussionunclassified
“…Ademais, um estudo (Eliason;Robinson;Balsam, 2017) Um ponto forte do presente estudo foi a utilização da versão validada para a população brasileira da NLS (Zanella et al, 2022), instrumento este que já vinha sendo utilizado sob tradução livre (Sampaio et al 2014;Sampaio et al, 2013;Flauzino et al, 2018). Este é o primeiro instrumento…”
Section: Discussionunclassified
“…The need for identification of the difficulties (observation of reality) that can be perceived by the individual is considered, as well as the influence of the beliefs of the individual during the observation of the individual's context, which implies in the preparation of theories about the problem (identification of key issues). Consequently, access to adequate information, at this time, can favor an understanding of the health situation of the individual (theorization) and the preparation of hypotheses (solution hypotheses), and accessible strategies following the reality of the individual (application to reality) (20)(21)(22) . In the present study, a gap was also observed in the health communication processes and such fact reinforces the hypothesis that this may also be a probable justification for these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they had difficulties in following the guidance related to diets and physical activities due to not fully understanding such guidance. In a global context, various studies have pointed out that socioeconomic factors and schooling levels are proxy variables and both related to the level of FHL (20)(21)(22) . This influences important aspects involved in the process of adherence to treatment and the self-care capacity (22,24) .…”
Section: Discussionmentioning
confidence: 99%
“…9 A Newest Vital Sign (NVS), também proposta com esse objetivo, é simples e sucinta e mostra-se ainda apropriada para avaliar o grau de LN. 10,11 Visto o entendimento de que o LN possui diversos domínios e da necessidade de uma ferramenta mais abrangente, aquela ideal para avaliar o LN ainda não está disponível. 12 Sabe-se que no Brasil, nas últimas décadas, a prevalência de obesidade cresceu significativamente, nos diferentes ciclos de vida, e vem repercutindo na incidência das Doenças Crônicas Não Transmissíveis (DCNT).…”
Section: Introductionunclassified